2022
DOI: 10.3390/life12020204
|View full text |Cite
|
Sign up to set email alerts
|

A 90-Day Safety Study of Meat from MSTN and FGF5 Double-Knockout Sheep in Wistar Rats

Abstract: MSTN and FGF5 gene knockout sheep generated by the CRISPR/Cas9 system exhibit the ‘double-muscle’ phenotype, and increased density and length of hairs, providing valuable new breeding material. In a previous study, we obtained MSTN and FGF5 double-knockout sheep of significant breeding value. In this study, we carried out a 90-day feeding study in Wistar rats to assess the safety of genome-edited mutton. Seven rat groups with 10 females and 10 males per group were fed different concentrations (3.75%, 7.5%, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…116 After performing routine urine and blood tests, examining blood biochemical indicators, weight, and histopathologically examining major organs, it was shown that all the investigated values were within the normal ranges, and consuming mutton from MSTN-edited sheep, with concentrations of 3.75%, 7.5%, and 15%, did not have any long-term adverse or toxic effects on rat health. 116 These results support the potential of meat from MSTN-edited sheep for future human consumption.…”
Section: ■ Targeting the Mstn Gene In Sheepmentioning
confidence: 93%
See 1 more Smart Citation
“…116 After performing routine urine and blood tests, examining blood biochemical indicators, weight, and histopathologically examining major organs, it was shown that all the investigated values were within the normal ranges, and consuming mutton from MSTN-edited sheep, with concentrations of 3.75%, 7.5%, and 15%, did not have any long-term adverse or toxic effects on rat health. 116 These results support the potential of meat from MSTN-edited sheep for future human consumption.…”
Section: ■ Targeting the Mstn Gene In Sheepmentioning
confidence: 93%
“…The trio-based sequencing approach revealed a low incidence of SNVs and Indels and almost negligible off-target modifications. Furthermore, a 90-day feeding study for the safety evaluation of meat from MSTN - FGF5 dual knockout sheep in Wistar rats was performed . After performing routine urine and blood tests, examining blood biochemical indicators, weight, and histopathologically examining major organs, it was shown that all the investigated values were within the normal ranges, and consuming mutton from MSTN -edited sheep, with concentrations of 3.75%, 7.5%, and 15%, did not have any long-term adverse or toxic effects on rat health .…”
Section: Targeting the Mstn Gene In Sheepmentioning
confidence: 99%
“…Previously, we prepared a MSTN and FGF5 double-knockout sheep by injecting Cas9 mRNA and sgRNA into zygotes, generating a MSTN and FGF5 dual-gene biallelic homozygous (MF −/− ) mutant (18). Here, we evaluated the reproductive capacity of MF −/− rams.…”
Section: Mstn and Fgf Double-knockout Does Not A Ect Semen Quality An...mentioning
confidence: 99%